0.17(0.5-x)=(0.1+x)(0.1+x)

Simple and best practice solution for 0.17(0.5-x)=(0.1+x)(0.1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.17(0.5-x)=(0.1+x)(0.1+x) equation:


Simplifying
0.17(0.5 + -1x) = (0.1 + x)(0.1 + x)
(0.5 * 0.17 + -1x * 0.17) = (0.1 + x)(0.1 + x)
(0.085 + -0.17x) = (0.1 + x)(0.1 + x)

Multiply (0.1 + x) * (0.1 + x)
0.085 + -0.17x = (0.1(0.1 + x) + x(0.1 + x))
0.085 + -0.17x = ((0.1 * 0.1 + x * 0.1) + x(0.1 + x))
0.085 + -0.17x = ((0.01 + 0.1x) + x(0.1 + x))
0.085 + -0.17x = (0.01 + 0.1x + (0.1 * x + x * x))
0.085 + -0.17x = (0.01 + 0.1x + (0.1x + x2))

Combine like terms: 0.1x + 0.1x = 0.2x
0.085 + -0.17x = (0.01 + 0.2x + x2)

Solving
0.085 + -0.17x = 0.01 + 0.2x + x2

Solving for variable 'x'.

Reorder the terms:
0.085 + -0.01 + -0.17x + -0.2x + -1x2 = 0.01 + 0.2x + x2 + -0.01 + -0.2x + -1x2

Combine like terms: 0.085 + -0.01 = 0.075
0.075 + -0.17x + -0.2x + -1x2 = 0.01 + 0.2x + x2 + -0.01 + -0.2x + -1x2

Combine like terms: -0.17x + -0.2x = -0.37x
0.075 + -0.37x + -1x2 = 0.01 + 0.2x + x2 + -0.01 + -0.2x + -1x2

Reorder the terms:
0.075 + -0.37x + -1x2 = 0.01 + -0.01 + 0.2x + -0.2x + x2 + -1x2

Combine like terms: 0.01 + -0.01 = 0.00
0.075 + -0.37x + -1x2 = 0.00 + 0.2x + -0.2x + x2 + -1x2
0.075 + -0.37x + -1x2 = 0.2x + -0.2x + x2 + -1x2

Combine like terms: 0.2x + -0.2x = 0.0
0.075 + -0.37x + -1x2 = 0.0 + x2 + -1x2
0.075 + -0.37x + -1x2 = x2 + -1x2

Combine like terms: x2 + -1x2 = 0
0.075 + -0.37x + -1x2 = 0

Begin completing the square.  Divide all terms by
-1 the coefficient of the squared term: 

Divide each side by '-1'.
-0.075 + 0.37x + x2 = 0

Move the constant term to the right:

Add '0.075' to each side of the equation.
-0.075 + 0.37x + 0.075 + x2 = 0 + 0.075

Reorder the terms:
-0.075 + 0.075 + 0.37x + x2 = 0 + 0.075

Combine like terms: -0.075 + 0.075 = 0.000
0.000 + 0.37x + x2 = 0 + 0.075
0.37x + x2 = 0 + 0.075

Combine like terms: 0 + 0.075 = 0.075
0.37x + x2 = 0.075

The x term is 0.37x.  Take half its coefficient (0.185).
Square it (0.034225) and add it to both sides.

Add '0.034225' to each side of the equation.
0.37x + 0.034225 + x2 = 0.075 + 0.034225

Reorder the terms:
0.034225 + 0.37x + x2 = 0.075 + 0.034225

Combine like terms: 0.075 + 0.034225 = 0.109225
0.034225 + 0.37x + x2 = 0.109225

Factor a perfect square on the left side:
(x + 0.185)(x + 0.185) = 0.109225

Calculate the square root of the right side: 0.330492057

Break this problem into two subproblems by setting 
(x + 0.185) equal to 0.330492057 and -0.330492057.

Subproblem 1

x + 0.185 = 0.330492057 Simplifying x + 0.185 = 0.330492057 Reorder the terms: 0.185 + x = 0.330492057 Solving 0.185 + x = 0.330492057 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.185' to each side of the equation. 0.185 + -0.185 + x = 0.330492057 + -0.185 Combine like terms: 0.185 + -0.185 = 0.000 0.000 + x = 0.330492057 + -0.185 x = 0.330492057 + -0.185 Combine like terms: 0.330492057 + -0.185 = 0.145492057 x = 0.145492057 Simplifying x = 0.145492057

Subproblem 2

x + 0.185 = -0.330492057 Simplifying x + 0.185 = -0.330492057 Reorder the terms: 0.185 + x = -0.330492057 Solving 0.185 + x = -0.330492057 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-0.185' to each side of the equation. 0.185 + -0.185 + x = -0.330492057 + -0.185 Combine like terms: 0.185 + -0.185 = 0.000 0.000 + x = -0.330492057 + -0.185 x = -0.330492057 + -0.185 Combine like terms: -0.330492057 + -0.185 = -0.515492057 x = -0.515492057 Simplifying x = -0.515492057

Solution

The solution to the problem is based on the solutions from the subproblems. x = {0.145492057, -0.515492057}

See similar equations:

| f(72)=-2(72)+23 | | (m^2+9)=0 | | 5+2(x-1)-3(1-x)=4+5(2x-3) | | 2t^2-20t-60=0 | | g(5)=12 | | (x+18)+4=x+(18+4) | | 1.085x=500 | | -5=x/15 | | 2t^2-12t-60=0 | | -16x^2+60x+6=6 | | (12-5i)/(3-2i) | | 0.78(1-x)(2-x)=x | | =-243x+3x | | 6x^2-1x=-1 | | ln(16x)/16x | | n^2+x-20=0 | | 64=(12.8/x)/(1/2) | | -1/4-4=7/4a-3 | | 3x-7=4-6 | | 7x-4=-x+36 | | 45b^4=25 | | F(30)=14-0.5x | | 4687.50=2070x+2721 | | y=2070(0.79)+2721 | | 6y+7=y+27 | | 3549+-1y=2070(x+-0.4) | | -.75y=.2 | | 3549-y=2070(x-0.8) | | 8x-3=5-4x | | 3.5+8*x=70.7 | | 1/3x3.14x36x15 | | 6/5=r/4 |

Equations solver categories